2017
DOI: 10.1080/15284336.2017.1311056
|View full text |Cite
|
Sign up to set email alerts
|

Virologic outcomes in early antiretroviral treatment: HPTN 052

Abstract: INTRODUCTION The HPTN 052 trial demonstrated that early antiretroviral therapy (ART) prevented 93% of HIV transmission events in serodiscordant couples. Some linked infections were observed shortly after ART initiation or after virologic failure. OBJECTIVE To evaluate factors associated with time to viral suppression and virologic failure in participants who initiated ART in HPTN 052. METHODS 1,566 participants who had a viral load (VL) >400 copies/mL at enrollment were included in the analyses. This inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Moreover, it has been shown that starting ART in the initial phase of infection might allow for the preservation of the immune system, and specifically of: (1) the CD4+ T-cell count and CD4/CD8 ratio [13][14][15]; (2) HIV-specific immune responses, preserving the ability to control viral replication [16]; (3) higher levels of mucosal and systemic Th17 cells; (4) lower levels of B-lymphocyte activation, and (5) reconstitution of the NK phenotype [12, 17 ,18]. Despite the fact that evidence from multiple studies strongly supports the benefit of early ART in AEHI [19][20], the optimal ART strategy to achieve rapid viral suppression, optimal immune recovery, and longer durability of regimens needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that starting ART in the initial phase of infection might allow for the preservation of the immune system, and specifically of: (1) the CD4+ T-cell count and CD4/CD8 ratio [13][14][15]; (2) HIV-specific immune responses, preserving the ability to control viral replication [16]; (3) higher levels of mucosal and systemic Th17 cells; (4) lower levels of B-lymphocyte activation, and (5) reconstitution of the NK phenotype [12, 17 ,18]. Despite the fact that evidence from multiple studies strongly supports the benefit of early ART in AEHI [19][20], the optimal ART strategy to achieve rapid viral suppression, optimal immune recovery, and longer durability of regimens needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Lower loss to follow‐up may increase the absolute number of PLWH achieving viral suppression (Pilcher 2017; Rosen 2016), reduce HIV transmission, and HIV‐related morbidity, and mortality (Eshleman 2017; Lesko 2016; Mfinanga 2015). The HIV continuum of care is however a complex process, in which every cascade step is influenced by multiple factors, as illustrated in our conceptual model (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Infected individuals remain infectious until they are diagnosed-it is then assumed that individuals are immediately treated such that they no longer are infectious and instead immune [20]. The time to diagnosis, or more precisely to successful treatment, is assumed to be exponentially distributed with rate γ common for all individuals (hence random and with no systematic heterogeneity).…”
Section: Plos Computational Biologymentioning
confidence: 99%